KAJIAN GENETIKA UNTUK KONSERVASI BADAK SUMATERA (DICERORHINUS SUMATRENSIS GLOGER, 1841) - Zein, Moch Syamsul Arifin; Fitriana, Yuli Sulistya; Kurniawan, Yuyun; Chaerani, Kurnia; Sirupang, Meriam (JURNAL BIOLOGI INDONESIA, 2019)
ABSTRACTThe Sumatran rhinoceros is one of the most critically endangered species of large mammals due to habitat loss, fragmentation and illegal hunting so that the population of this species drastically decreased. At present, reproductive problems with a limited population are also a threat and require an appropriate solution. Therefore, data on molecular genetic information is very important as a basis for conservation management in maintaining long-term persistence of this species. Phylogenetic analysis based on sequences of CO1, 12SrRNA, and Cytochrome b gen from mitochondrial DNA genomes using neighbor-joining and genetic distance matrix calculations with the Kimura 2-parameter model (K2P) were implemented in pairwise distance calculations in the Mega (Molecular Evolutionary Genetics Analysis) program version 6.05. The study results show the genetic distance of Sumatran Rhinos from Sumatra and Kalimantan respectively 0.2 ± 0.00%, 0.8 ± 0.4%, and 0%. These results were reconfirmed that the Sumatran Rhino species in Sumatra and Kalimantan were taxonomy is no different. The study of genetic diversity based on D-loop of mitochondrial DNA contained 5 haplotypes, namely haplotypes 1 and 2 originating from the island of Sumatra and haplotypes 3, 4, and 5 originating from the island of Borneo. The genetic distance between individuals in this study ranged from 2.54 ± 1.4%, haplotype diversity (Hd) was 0.8 ± 0.172, nucleotide diversity (Pi) was 0.02269, Fu?s Fs value was 2.523, and Tajima?s test was 0.69497. The positive value (Fu?s Fs and Tajima?s test) indicated low genetic diversity and population expansion in the Sumatran rhino. In the study using 10 microsatellite loci, where the average number of allel/loci in Kalimantan (1.68) was higher than in Sumatra (1.22). Data from this study show that genetic variation between Sumatran rhinoceros from Sumatra and Kalimantan can be used as a basis for alternative that the populations of Sumatra and Borneo be considered as a single management unit.  Keywords: Sumateran  Rhinoceros, Mitochondrial DNA, Microsatellite